(untitled) (Journal of Economic Research & Business Administration, 2019)
The article defines the place, importance and infrastructural elements of food security in ensuring national security of the state; the conditions forming food security of the country are designated. The importance of the implementation of mechanisms to ensure food security in accordance with the Doctrine of food security of Russia: increasing the availability of food for all groups of the population; the formation of a healthy type of food; production and turnover of agricultural, fish products and food; organization and management of food security. The purpose of the article is to determine the conditions that shape the food security of the country and the structuring of the elements of the food security system. For achieving the goal, comparative, dialectic, historical methods, system-structural and comparative-legal analysis are used. It is noted that the key elements of the food security system are rational consumption norms, food safety, physical accessibility of food products, economic accessibility of food products, development of economic potential and reduction of crime in agriculture, food independence. The levels of food security are considered in detail: global, interethnic, state, regional from the position of the subject solving the problems and mechanisms of food security. The authors point to the special role of individual industries and industries involved in ensuring food security of the state, in particular, the conclusion is made about the need to develop the agricultural industry and food industry in order to improve the quality of domestic production to ensure food security of the state.